Digital formations : IT and new architectures in the global realm - Latham, Robert, 1956-; Sassen, Saskia (Princeton University Press, 2005)
Computer-centered networks and technologies are reshaping social relations and constituting new social domains on a global scale, from virtually borderless electronic markets and Internet-based large-scale conversations to worldwide open source software development communities, transnational corporate production systems, and the global knowledge-arenas associated with NGO networks. This book explores how such "digital formations" emerge from the ever-changing intersection of computer-centered technologies and the broad range of social contexts that underlie much of what happens in cy